Problems of intensification of bank lending to the real sector of the economy in the conditions of martial law - Dziubliuk, Oleksandr (Herald of Economics, 2023)
Introduction. The difficult conditions of the economic situation in Ukraine during the period of martial law directly affected the activities of the banking system in terms of credit provision for the production and consumer needs of all market subjects, although problematic moments in the field of bank lending did not arise with the start of full-scale war, but accumulated over a quite long period time. Under such circumstances, the study of the main problems arising in the field of bank lending to the real sector should be considered particularly relevant, so that the functioning of banks in the conditions of martial law is stable and maximally provides the needs of the national economy in terms of credit resources.Purpose. The purpose of the study is to find out the main trends and problems of the organization of bank lending to the economy in the conditions of martial law and, on this basis, determine possible directions for optimizing the credit relations of banks with clients for the effective redistribution of monetary resources in favor of the real sector and contributing to the stabilization of the economic situation in the country.Methods. The methods of the system approach and generalization of data are used to assess trends and regularities in the organization of credit relations. In addition, general scientific and empirical techniques and tools of economic science, methods of analysis and synthesis, comparison, summary and grouping were used.Results. The main trends in the functioning of commercial banks on the credit market and the specific of the formation of the structure of bank assets are studied. Factors affecting the credit activity of the banking system under martial law are systematized. The actions of the National Bank to stimulate the work of the banking sector in lending to the economy are analyzed. The main directions of economic policy, which are necessary as a set of measures for the activation of bank lending to the real sector, are substantiated.Prospects. It is advisable to focus further scientific research on the assessment of the macroeconomic conditions for the effective functioning of the credit mechanism, in particular regarding ensuring the stable value of the national currency, preventing crisis phenomena in the banking system, and reliable legal protection of the interests of banks as creditors.